Effect of TiBAl inoculation on abrasive wear resistance of high Cr white cast iron - Teker, Tanju; Yilmaz, S. Osman; Kerkut, Erhan (Carl Hanser Verlag, 2019)
High chromium white cast iron (HCrWCI) is generally used in applications requiring superior wear resistance. The alloys were inoculated with 1-3 wt.-% TiBAl to rearrange the crystallography of the carbides. The alloys were subject toheat treatment at 1000 degrees C for 1 and 2 h. The microstructuresof the alloys was examined by SEM. Chemical composition was determined by EDS. For wear tests, alloys were tested using 10, 20 and 30 N loads under pin-on-disc wear conditions. Worn surfaces of the alloys were analyzed by SEM. The worst wear resistance was obtained in the alloy inoculated with 3 wt.-%. TiBAl.
Keywords: High Cr white cast iron; TiBAl; inoculation; wear resistance